Rigid ureteroscopy - Rudney, Jerry (Operating Room Nurses Association of Canada Journal, 1988)
The introduction of extracorporeal shockwave lithotripsy (ESWL) in the treatment of ureteral calculi has proven to be safe and effective. Even though ESWL has gained acceptance as the primary choice of intervention, there are still many occasions when rigid and/or ﬂexible ureteroscopy is necessary in the treatment of these calculi and other ureteral pathology situations.1